2014
DOI: 10.1155/2014/381501
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Salt-Stress-Induced Genes from the RNA-Seq Data ofReaumuria trigynaUsing Differential-Display Reverse Transcription PCR

Abstract: Next generation sequencing (NGS) technologies have been used to generate huge amounts of sequencing data from many organisms. However, the correct choice of candidate genes and prevention of false-positive results computed from digital gene expression (DGE) of RNA-seq data are vital when using these genetic resources. We indirectly identified 18 salt-stress-induced Reaumuria trigyna transcripts from the transcriptome sequencing data using differential-display reverse transcription PCR (DDRT-PCR) combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Recently, the application of transriptomics in recretohalo phytes enhances the discovery of candidate genes involved in salt secretion. The transcription profiles of the recretohalophyte R. trigyna indicated that the genes related to ion transport were relevant to the salt secretion function of this species ( Dang et al, 2013 , 2014 ). Similarly, the candidate genes encoding ion transporters were also suggested in Sporobolus virginicus by RNA-seq ( Yamamoto et al, 2015 ).…”
Section: A Possible Pathway For Secreting Salt From the Salt Glandmentioning
confidence: 99%
“…Recently, the application of transriptomics in recretohalo phytes enhances the discovery of candidate genes involved in salt secretion. The transcription profiles of the recretohalophyte R. trigyna indicated that the genes related to ion transport were relevant to the salt secretion function of this species ( Dang et al, 2013 , 2014 ). Similarly, the candidate genes encoding ion transporters were also suggested in Sporobolus virginicus by RNA-seq ( Yamamoto et al, 2015 ).…”
Section: A Possible Pathway For Secreting Salt From the Salt Glandmentioning
confidence: 99%
“…Generally, stress results in changes in the cellular program that involve significant transcriptional alterations aimed at increasing the chances of survival (Diédhiou et al, 2008). A study by Dang et al (2014) proved that overexpression of GmPAP3 improved rice salt tolerance by increasing the ROS-scavenging ability and decreasing oxidative damage. Similarly, a possible tolerance role of GmPAP3 under oxidative stress was demonstrated in soybean, indicating that the GmPAP3 gene expression is regulated by salinity, osmotic, and oxidative stresses (Liao et al, 2003;Li et al, 2008b;Soleimani et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The use of transcriptomics in recretohalophytes has helped uncover candidate genes involved in salt secretion. Candidate genes encoding ion transporters have been identified in the recretohalophytes R. trigyna (Dang et al 2013(Dang et al , 2014, Sporobolus virginicus (Yamamoto et al 2015), and L. bicolor (Yuan et al 2016b) via RNA-seq of plants under different NaCl treatments. Proteomics has also accelerated the investigation of salinity-responsive proteins in recretohalophytes.…”
Section: Modern Molecular Biology Sheds Light On the Mechanism Of Salt Secretion From Salt Glandsmentioning
confidence: 99%